Aspectos estéticos e estilísticos das Sonatas de Glauco Velásquez - Silva, Agata Christie Rodrigues Lima da (2020)
Glauco Velásquez's four sonatas present a demonstration of the stylized experiments carried out by this composer. Written between 1909 and 1912, they will be studied in Sonata “Delírio”, Op.61, 1909, for violin and piano, Sonata I (“Appassionata”), 1910, for cello and piano, in Sonata 2, Op.82, 1911, for violin and piano and Sonata II, 1912, for cello and piano. The present work presents an observation dedicated to the elements arranged in Glauco Velásquez's speech to understand his aesthetics and influences. These four sonatas demonstrated a complexity created at different times in the short life of the composer. However, the scope of this study reached only the first movement of each piece added to the historicalsociological contributions, central part of the discursive investigation. In general, the works have characteristics typical of the post-tonal repertoire marked by a dense contrapuntal texture and an occasional singable sound. The sonatas “Delirio” and 2, for violin and piano, are considered with great lyricism, in contrast to a virtuosic sonority of the sonatas “Appassionata” and Sonata II, for cello and piano. The four works combine style and expressiveness and carry an intense poetic-expressive aspect. It will be observed the ways that Glauco Velásquez uses his musical definitions in his discreet language.